Geographic differences in the distribution of manufacturing firms in Ontario, Canada. Issue 3 (11th March 2020) - Arku, Godwin; Cleave, Evan; Easton, Megan
Abstract : For at least the past 20 years, the Province of Ontario – as well as other advanced economic regions – has experienced a period of transition, with traditional manufacturing declining and advanced manufacturing firms and sectors emerging. Concurrently, there has been a concerted policy effort emphasising the development of industry clusters within the province, though key issues of governance and where and how to invest public funds remain. This paper presents research on the spatial configuration of firms in 26 manufacturing sub‐sectors, using point density analysis of the basis for determining the presence and spatial configuration of firms. This allows for the comparison of patterns observed in traditional, advanced, and evolving sub‐sectors. The findings show that there are patterns of clustering in all sub‐sectors, though different spatial configurations are apparent between traditional, advanced, and evolving sub‐sectors. These differences have implications for both investment and governance. Based on the findings, investment needs to be directed towards areas with locational advantages, while regional perspectives and initiatives on cluster governance are needed. Abstract : This paper examines the spatial configuration of manufacturing in the Province of Ontario, Canada. Though firms across the 26 manufacturing sub‐sectors analysed in this study were found to cluster, there were identifiable differences in the spatial distribution and the characteristics of these clusters. This is, in part, due to differences in the evolution and life‐cycles of these manufacturing sub‐sectors and their clusters.